Impact of some physical exercises in the development of the completion of the decimal games of students fourth stage - Shaghati, Ahlam; Nagi, Ahmed (Journal of Physical Education, 2014)
The importance of the search from came from implemented physical exercises, which are consistent with the nature and circumstances of event to achieve development level of fitness and performance of decathlon skills. The problem lies in need to develop some physical qualities of the students how practicing decathlon, effectively to achieve the best level of performance skills through their academic years. Study’s aim: • To develop training program for physical exercises. • To know the level of skill and physical performance among a sample search. • To The effect physical exercisesto to level of skill a and physical performance for performing. The most important assumptions: • Post and pretests to know the level of development and physical d skills among students how are researches sample. Research procedures: The research procedure applied to the study on a sample of students (male) from their first academic year 2013-2014 has been selected, from Physical Education College/ University of Baghdad, AL- Jadiriya. The researcher conducting tests before and after and the duration (8) weeks of the program by two units a week, the performance level has been shown through results analysis of this study, that the effect of the exercises indicate progress in physical skill and efficiency in decathlon event at the students. The researcher recommends emerge physical exercises in training of the efficiency of decathlon event.